The Role of MicroRNA in DNA Damage Response - Li, Yongxin; Tong, Yan; Liu, Jiaqi; Lou, Jianlin (Frontiers in Genetics, 2022)
DNA is essential for the development and function of organisms. A number of factors affect DNA integrity and cause DNA damage, such as ultraviolet light, ionizing radiation and hydrogen peroxide. DNA damages activate a series of intracellular reactions, called DNA damage response, which play a crucial role in the pathogenesis of cancers and other diseases. MiRNA is a type of evolutionarily conserved non-coding RNA and affects the expression of target genes by post-transcriptional regulation. Increasing evidences suggested that the expression of some miRNAs was changed in tumor cases. MiRNAs may participate in DNA damage response and affect genomic stability via influencing the processes of cell cycle, DNA damage repair and apoptosis, thus ultimately impact on tumorigenesis. Therefore, the role of miRNA in DNA damage response is reviewed, to provide a theoretical basis for the mechanism of miRNAs’ effects on DNA damage response and for the research of new therapies for diseases.